Combine effect of fly ash and aggregate size on flexural strength of reinforced concrete - Kumar, Dileep; Vikrant, Dhanik; Memon, Kashif Rafique; Mandokhail, Alyas Khan (Mehran University research journal of engineering and technology, 2025)
The study emphasizes the importance of utilizing fly ash and optimized aggregate sizes to enhance structural performance while promoting sustainable construction practices by reducing cement usage. In this research study, the combined effect of fly ash and aggregate size on the flexural strength of reinforced concrete is investigated. In this experimental study, a total of 12 batches were prepared with varying fly ash proportions and coarse aggregate sizes. For all batches, cement was replaced with fly ash by 0%, 5%, 10%, and 15% by weight of cement, and three different sizes of coarse aggregates (6.25 mm, 12 mm, and 20 mm) were used. The mix design and water cement ratios were set to (1:2:4) and 0.48, respectively. Prism-type RCC beams of size 100mm x 100mm x 500mm were casted for testing to evaluate density, ultimate load, and ultimate strength. Results revealed that reinforced concrete batch B2, containing 5% fly ash and 12.5 mm aggregate size, achieved a higher density and sustained an ultimate load 56.48% higher than nominal concrete. Furthermore, deflection in reinforced concrete batch D1 containing 15% fly ash and 20-mm aggregate size decreased by 12.13% compared to nominal concrete. The results showed that the combined effect of fly ash and aggregate size will minimize deflection and will provide sufficient flexural strength to sustain structural load effectively.